Nonlinear and Adaptive State Feedback Control of Variable Speed PMSM Drives - Hasirci, Ugur; Balıkçı, Abdulkadir (IEEE, 2009)
This paper deals with design of a nonlinear adaptive state feedback controller for a Permanent Magnet Synchronous Motor (PMSM). We firstly present an exact model knowledge controller that ensures the exponentially tracking of a time-varying velocity profile and after this, it is modified to an adaptive controller that satisfies the velocity tracking error signal converges to zero with small control gains despite the uncertainties in motor dynamics. Lyapunov based analysis approach is used to determine stability and performance results. Numerical simulations for the exact model knowledge and the adaptive controllers are presented to demonstrate the performance and feasibility of proposed method.
7th Asian Control Conference (ASCC 2009) -- AUG 27-29, 2009 -- Hong Kong, PEOPLES R CHINA
Keywords: Magnet Synchronous Motor; Permanent-Magnet; Design